Evaluation of different adjuvants for foot-and-mouth disease vaccine containing all the SAT serotypes - M. Cloete; B. Dungu; L.I. Van Staden; N. Ismail-Cassim; W. Vosloo (Onderstepoort Journal of Veterinary Research, 2008)
Foot-and-mouth disease (FMD) is an economically important disease of cloven-hoofed animals that is primarily controlled by vaccination of susceptible animals and movement restrictions for animals and animal-derived products in South Africa. Vaccination using aluminium hydroxide gel-saponin (AS) adjuvanted vaccines containing the South African Territories (SAT) serotypes has been shown to be effective both in ensuring that disease does not spread from the endemic to the free zone and in controlling outbreaks in the free zone. Various vaccine formulations containing antigens derived from the SAT serotypes were tested in cattle that were challenged 1 year later. Both the AS and ISA 206B vaccines adjuvanted with saponin protected cattle against virulent virus challenge. The oilbased ISA 206B-adjuvanted vaccine with and without stimulators was evaluated in a field trial and both elicited antibody responses that lasted for 1 year. Furthermore, the ISA 206 adjuvanted FMD vaccine protected groups of cattle against homologous virus challenge at very low payloads, while pigs vaccinated with an emergency ISA 206B-based FMD vaccine containing the SAT 1 vaccine strains were protected against the heterologous SAT 1 outbreak strain.